2009
DOI: 10.1016/j.conbuildmat.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various dual-phase heat treatments on the corrosion behavior of reinforcing steel used in the reinforced concrete structures

Abstract: In this study, corrosion behavior of six different dual-phase (DP) steels with varying morphologies and martensite content has been examined in comparison to ferrite-pearlite steel in concrete. Intercritical annealing and intermediate quenching heat treatments have been applied to the reinforcing steel in order to obtain DP steels with different morphologies and content of martensite. Corrosion experiments were conducted in two stages. In the first stage, the corrosion potential of steels embedded in concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 8 publications
2
28
0
1
Order By: Relevance
“…Bhagavathi et al 2 studied the mechanical properties and corrosion behavior of dual-phase steels and found that by increasing the martensite volume fraction (MFV), the UTS of dual-phase steels increased and corrosion rate of DP steel samples marginally decreased compared to that for the low alloy steel sample. Kelestemur et al 11 showed that the corrosion rate of dual phase steel has increased with increasing the amount of martensite. Sarkar et al 6 studied the electrochemical behavior of microalloyed dual phase steels and found that an increase in martensite content and structural refinement, decreases the corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Bhagavathi et al 2 studied the mechanical properties and corrosion behavior of dual-phase steels and found that by increasing the martensite volume fraction (MFV), the UTS of dual-phase steels increased and corrosion rate of DP steel samples marginally decreased compared to that for the low alloy steel sample. Kelestemur et al 11 showed that the corrosion rate of dual phase steel has increased with increasing the amount of martensite. Sarkar et al 6 studied the electrochemical behavior of microalloyed dual phase steels and found that an increase in martensite content and structural refinement, decreases the corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of carbonitriding treatment, a higher resistance is evident when compared to the above cases, dueto the forming of iron nitrate onthe surface, and followed by a cementite layer at the grain boundaries which forms a thick surface protection layer with a gradient hardness [11].…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have indicated that both the chemical composition and the microstructure of the reinforcing steel have an impact on its corrosion performance, even within the type of steels typically denoted "mild steel" or "carbon steel" [3][4][5][6][7][8]. Thus, it is important to adequately report the relevant information.…”
Section: Experimental Details To Be Considered In Studies Of Corrosiomentioning
confidence: 99%